A Facile One‐Step Method for the Synthesis of Reduced Graphene Oxide Nanocomposites by NADH as Reducing Agent and Its Application in NADH Sensing. Issue 1 (9th October 2013) - Tabrizi, Mahmoud Amouzadeh; Zand, Zahra
Abstract Here, we report a green and eco‐friendly approach to synthesize reduced graphene oxide (rGO) via a mild hydrothermal process using nicotinamide adenine dinucleotide (NADH) as a reducing agent. The obtained rGO was characterized by UV‐visible absorption spectroscopy (UV‐vis), X‐ray diffraction spectroscopy, atomic force microscopy (AFM) and scanning electron microscopy (SEM). Electrochemical experiments indicated that the rGO/GC electrode exhibited an excellent electrocatalytic activity towards the oxidation of NADH, which can be attributed to the excellent electrical conductivity and high specific surface area of the rGO composite. The resulting biosensor showed highly sensitive amperometric response to NADH with a low detection limit (0.6 µM).